Analisis Kepekaan Sosial Siswa terhadap Siswa Berkebutuhan Khusus di Sekolah Penyelenggara Pendidikan Inklusi - Sindy Ayu Lestari Romadhoni; Arya Setya Nugroho (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The abundance of differences often makes them feel like outsiders. The environment around the child will greatly influence the child's social sensitivity. Inclusive schools are a means of increasing children's social sensitivity because they include children with special needs who can practice caring for others. However, The existence of inclusive school programs is often considered a hindrance because when children with disabilities are placed in the same educational environment as their typically developing peers, they may feel uncomfortable and are sometimes underestimated. This research aims to analyze and describe social sensitivity in children towards conditions different from their own while studying at the same school, namely SD Muhammadiyah 1 GKB.This study focuses on the social sensitivity of elementary school students. The approach used in this research is qualitative with a descriptive method. Secondary data is used to collect research data, employing observation and interviews as data collection techniques. The results of this study indicate that inclusive education provides various benefits, one of which is the emergence of social sensitivity in children such as a sense of empathy, sympathy, help and respect for differences.